Understanding thrombosis: the critical role of oxidative stress - Peiming Li; Xueru Ma; Guofei Huang (Hematology)
Thrombosis, a leading contributor to global health burden, is a complex process involving the interplay of various cell types, including vascular endothelial cells, platelets, and red blood cells. Oxidative stress, characterized by an overproduction of reactive oxygen species (ROS), can significantly impair the function of these cells, thus instigating a cascade of events leading to thrombus formation. In this review, we comprehensively explore the role of oxidative stress within these cells, and its mechanistic contribution to thrombogenesis, and the application of oxidative therapy in inhibiting thrombosis. By dissecting the intricacies of oxidative stress and its impact on thrombosis, we underscore its potential as a viable therapeutic target. Therefore, further research in this direction is warranted to enhance our understanding and management of thrombotic disorders.